TQM Practices in Manufacturing and Service Companies in Peru - Pino, Ricardo M. (Pontificia Universidad Católica del Perú. CENTRUM, 2008)
The research study involved exploring how Peruvian companies use TQM practices and the differences in this use considering industrial sector and company size. Three hundred and sixty-three MBA students, middle managers of private companies operating in Arequipa, Cajamarca, Chiclayo, Cusco, Lima, Piura, or Trujillo, answered a questionnaire, developed by the author, about the use of TQM practices in their companies. The findings indicate significant differences between manufacturing and service companies in two practices, information and analysis and empowerment; and significant differences among small, medium, and large companies in two practices, information and analysis, and employee training.
Keywords: Peru; TQM; Company size; Industrial sector; Quality; https://purl.org/pe-repo/ocde/ford#5.02.04